Biodiversity Offsets : A User Guide - World Bank Group (World Bank, Washington, DC, 2016)
Biodiversity represents the variety of life on Earth, including the full range of ecosystems, species, and genes. Biodiversity conservation efforts to date have achieved a great deal to help secure the continued functioning of many threatened ecosystems and the survival of numerous species. Biodiversity offsets can: (i) improve the conservation outcomes from large-scale development projects, and (ii) provide much-needed funding for protected areas and similar conservation efforts. This user guide provides introductory guidance on whether, when, and how to prepare and implement biodiversity offsets for large-scale, private, and public sector development projects. It also explores some of the opportunities that may exist for developing national biodiversity offset systems.